Analisis Metode RGEC Terhadap Harga Saham - Alfa Rahmiati; Gamaniar Putri Islamie (Jurnal Proaksi, 2024)
Stocks are a type of financial instrument that investors find attractive because they offer significant returns with moderate risk. Stock prices are influenced by several things, namely how well a company carries out its financial activities, as shown in its financial statements. This study was conducted to see the effect of bank health on stock prices by analyzing RGEC which uses LDR, GCG, ROA, and CAR measurements in bank health to see its effect on stock prices. Banking plays an important role in the economic cycle in the country. This study uses multiple analysis techniques using secondary data from conventional banking on (BEI) for the 2019-2021 period. The sample determined using the purposive sampling method was 72 observations. the results of the study were carried out, the conclusion was that Risk Profile, GCG and Capital did not affect stock prices, Earnings affected stock prices.